Reanalysis of offshore T-joint fatigue life predictions based on a complete weld profile model - Lozano-Minguez, Estívaliz; Brennan, Feargal Peter; Kolios, Athanasios J. (Elsevier, 2014)
A comparison between the fatigue life predictions obtained by the stress concentration factors (SCFs) of 3D solid finite element (FE) models considering the weldment and the existing SCF parametric equations for tubular T-joints, is presented in this paper. From the study carried out, it was concluded that the existing parametric equations for predicting hot spot SCFs are very conservative and insufficient to be used for optimisation. SCFs should be carried out by modelling 3D solid joints which include the weldment and should be based on notch stresses measured on the external surface at the weld toe. The Offshore and Marine Renewable Energy industry could significantly reduce their investment costs using contemporary FE models, since slight overestimations of the SCF results in a corresponding large reduction in predicted service life.
Keywords: Stress concentration factors; Hot spot stress; Notch stress; Fatigue life predictions; Tubular T-joints; Offshore support structures